Retinol-Binding Protein Interferes with Transthyretin-Mediated β-Amyloid Aggregation Inhibition - Mangrolia, Parth (Biochemistry, 2018)
β-Amyloid (Aβ) aggregation is causally linked to Alzheimer’s disease. On the basis of in vitro and transgenic animal studies, transthyretin (TTR) is hypothesized to provide neuroprotection against Aβ toxicity by binding to Aβ and inhibiting its aggregation. TTR is a homotetrameric protein that circulates in blood and cerebrospinal fluid; its normal physiological role is as a carrier for thyroxine and retinol- binding protein (RBP). RBP forms a complex with retinol, and the holoprotein (hRBP) binds with high affinity to TTR. In this study, the role of TTR ligands in TTR-mediated inhibition of Aβ aggregation was investigated. hRBP strongly reduced the ability of TTR to inhibit Aβ aggregation. The effect was not due to competition between Aβ and hRBP for binding to TTR, as Aβ bound equally well to TTR–hRBP complexes and TTR. hRBP is known to stabilize the TTR tetrameric structure. We show that Aβ partially destabilizes TTR and that hRBP counteracts this destabilization. Taken together, our results support a mechanism wherein TTR-mediated inhibition of Aβ aggregation requires not only TTR–Aβ binding but also destabilization of TTR quaternary structure.